Identification and characterization of a potential strain for the production of polyhydroxyalkanoate from glycerol - Xue, Mengheng; Huang, Rong; Liu, Wei; Cheng, Jian; Liu, Yuwan; Zhang, Jie; Wang, Limei; Liu, Dingyu; Jiang, Huifeng (Frontiers in Microbiology, 2024)
While poly(3-hydroxybutyrate) (PHB) holds promise as a bioplastic, its commercial utilization has been hampered by the high cost of raw materials. However, glycerol emerges as a viable feedstock for PHB production, offering a sustainable production approach and substantial cost reduction potential. Glycerol stands out as a promising feedstock for PHB production, offering a pathway towards sustainable manufacturing and considerable cost savings. The identification and characterization of strains capable of converting glycerol into PHB represent a pivotal strategy in advancing PHB production research. In this study, we isolated a strain, Ralstonia sp. RRA (RRA). The strain exhibits remarkable proficiency in synthesizing PHB from glycerol. With glycerol as the carbon source, RRA achieved a specific growth rate of 0.19 h -1 , attaining a PHB content of approximately 50% within 30 hours. Through thirdgeneration genome and transcriptome sequencing, we elucidated the genome composition and identified a total of 8 genes (glpR, glpD, glpS, glpT, glpP, glpQ, glpV, glpK) involved in the glycerol metabolism pathway. Leveraging these findings, the strain RRA demonstrates significant promise in producing PHB from low-cost renewable carbon sources.